ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK - Talsyah Syahidiah; Nita Hidayati (IKIP Siliwangi, 2022)
The purpose of this study is to describe, analyze, and interpret mathematical problem solving skills with absolute value equations and inequalities. This study uses a descriptive qualitative research design. This research was conducted in one of the SMA/MA in the city of Karawang, with the research subjects of 29 students of class X MIPA who had studied absolute value equations and inequalities. The data collection technique of this research is a written test instrument in the form of a description with a total of four questions. Before starting the data analysis, the validity of the questions has been done first. Based on the research findings, there are various kinds of errors in solving problems involving absolute value equations and inequalities. On the indicator of understanding the problem getting 22.8%, indicators implementing plans 15.1%, indicators completing plans 45.2%, and indicators checking back as much as 17%. Therefore, the mathematical problem solving ability of X MIPA students in one of the SMA/MA in Karawang city is classified as moderate in all indicators of mathematical problem solving ability.